ANALISIS KEUNGGULAN KOMPARATIF BAWANG MERAH (Allium ascalonicum L.) DI DESA NGANTRU, KECAMATAN NGANTANG, KABUPATEN MALANG - Umbu Tamu, Marselinus Roberto; Arvianti, Eri Yusnita; Pudjiastuti, Agnes Quartina (Fakultas Pertanian, 2017)
Red onion produced in almost all parts of Indonesia. The main producing red onion north Sumatra, West Sumatra, West Java, Central Java, East Java, West Nusa Tenggara, Central Sulawesi and South Sulawesi. The purpose of this study was to analyze the comparative advantages of onion businesses in Ngantru village. This research is a qualitative research with methods of analysis used was the analysis of Domestic Resources Cost (DRC). The population in this study was 60 and 30 samples. The sampling technique used random sampling while the data collection took place in January-June 2016 using questionnaires.Results of statistical analysis showed that onion farming in the village of Ngantru, Ngantang, Malang Regency experienced excellence both private (6,652,221,805) and social advantages (39.1307 billion) calculations.This meant that onion farming was efficient and it could be concluded of having competitive value for the benefit of farmers and have comparative advantages. From two indicators measuring competitiveness: cost ratio of private (private cost ratio or PCR) showed that onion farming was more competitive with PCR